2020
DOI: 10.1183/23120541.00721-2020
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative tuberculosis/HIV activities in the European Region

Abstract: IntroductionAn estimated 12% of tuberculosis (TB) patients are coinfected with HIV in the World Health Organisation European Region (Region). Reducing morbidity and mortality from HIV-associated TB requires strong collaboration between TB and HIV services at all levels with integrated people-centred models of care.MethodsWe collected information on the current models of integration of TB and HIV services in the Region via a comprehensive survey among the TB and HIV National Focal Points, and identified challen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…In the vast majority (79%), care was initiated at special TB hospitals [39]. The testing of all TB patients for HIV was recommended in 85%, while the screening for active TB in all PLWH was recommended in 72% of official national guidelines across Europe [71]. Furthermore, a majority of countries (64%) recommended latent TB infection (LTBI) screening in all PLWH [71].…”
Section: Problem 5: Fragmented Healthcare Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the vast majority (79%), care was initiated at special TB hospitals [39]. The testing of all TB patients for HIV was recommended in 85%, while the screening for active TB in all PLWH was recommended in 72% of official national guidelines across Europe [71]. Furthermore, a majority of countries (64%) recommended latent TB infection (LTBI) screening in all PLWH [71].…”
Section: Problem 5: Fragmented Healthcare Systemsmentioning
confidence: 99%
“…The testing of all TB patients for HIV was recommended in 85%, while the screening for active TB in all PLWH was recommended in 72% of official national guidelines across Europe [71]. Furthermore, a majority of countries (64%) recommended latent TB infection (LTBI) screening in all PLWH [71]. Provision of care was standardized by relying on national guidelines in all healthcare centres surveyed in eastern Europe, while only 57% of those centres also relied on WHO or European AIDS clinical society guidelines [39].…”
Section: Problem 5: Fragmented Healthcare Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, guidelines in low-incidence countries have varied in their recommendations—for example, in a multi-country study on TB/HIV collaborative policies in European countries, in which 47 countries participated, it was reported that 21 (62%) recommended screening all PLHIV for TB, while 13 (38%) recommended selective screening. The criteria for selective screening included previous contact with a TB case, TB symptoms, previous history of TB and low CD4+ cell count (< 350 cells/μL) [ 19 ]. The most recent guideline from the European AIDS Clinical Society has recommended routine screening using chest X-ray (CXR) for PLHIV from high TB prevalence populations [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“… 4 The European Centre for Disease Prevention and Control (ECDC) also notes that other concerns regarding Ukraine's population including (second highest number of tuberculosis cases in Europe), HIV (the second-highest prevalence of HIV/TB coinfection in the World Health Organization European Region), and seasonal flu in Ukraine. 8 , 9 It also announced that traumatic wounds infected by multi-drug resistant organism during the invasion of Ukraine that could be transmitted in other European territories. 10 In summary, the recent Russo-Ukrainian war has raised concern about preventive measures about COVID-19 pandemic.…”
mentioning
confidence: 99%